2004
DOI: 10.1002/pen.20035
|View full text |Cite
|
Sign up to set email alerts
|

Bubble removal in rotational molding

Abstract: Closed form solutions have been obtained for bubble dissolution in typical polymer melts encountered in rotational molding. The solutions are in excellent agreement with experimental data available in the literature. Using these solutions, it is shown that under typical rotational molding conditions the polymer melts may be almost saturated. As a result, bubble shrinkage occurs over long periods. Depending on the degree of saturation, surface tension may contribute substantially to the concentration gradient t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 4 publications
1
55
0
Order By: Relevance
“…Thus, it has reached a wide application [3,4], and also drawn more attentions from researchers to further optimize its fabrication process as well as the formed part's performance. In this regard, Spence and Gogos did some investigations on the bubble defect in a rotationally molded part [5,6]. Lim et al adopted numerical analysis method to predict the temperature distribution in the mold [7].…”
Section: Introductionmentioning
confidence: 98%
“…Thus, it has reached a wide application [3,4], and also drawn more attentions from researchers to further optimize its fabrication process as well as the formed part's performance. In this regard, Spence and Gogos did some investigations on the bubble defect in a rotationally molded part [5,6]. Lim et al adopted numerical analysis method to predict the temperature distribution in the mold [7].…”
Section: Introductionmentioning
confidence: 98%
“…These cavities form due to gas, which is trapped during sintering [2,[9][10][11][12]. The time to remove these inclusions is, among others, determined by the size of the inclusions and thereby by the amount of gas within the inclusions [2,[9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Viscoelastic relaxation has a pronounced effect on the time scales of the shrinkage process in the simulation but does not alter the equilibrium pore radius. A first attempt at including gas diffusion was made motivated by the works of Kontopoulou and Vlachopoulos [4] and Gogos [5]. Numerical solutions of a simplified model showed that, depending on the time scales of the diffusion process, diffusion can have a significant influence on viscoelastic polymer sintering and that the pressure inside the pore reaches high values without diffusion or with slow diffusion.…”
Section: Conclusion and Outlinementioning
confidence: 99%
“…Separate models for the diffusive dissolution of gaseous pores in polymer melts have been presented [4], [5]. These do however either model flow processes as purely viscous or neglect them completely.…”
Section: Introductionmentioning
confidence: 99%